New Perspectives in Neurosteroids action: a Special Player Allopregnanolone - Valerio Magnaghi (Frontiers Research Topics, 2015)
Early in the 80's date the first observations on the existence of hormonal steroids that may be synthesized and act in the nervous system. In order to refer to these endogenous steroids, proved important to control both central and peripheral nervous system, it was proposed the term "neurosteroids" (NSs). Over the years, their importance in regulating the physiological functions of neuronal and glial cells increased progressively. These steroids can be involved in several pathophysiological conditions such as depression, anxiety, premenstrual syndrome (PMS), schizophrenia and Alzheimer disease. Among the different classes of NSs, the progestagens revealed particularly important. The progesterone metabolite 5a-pregnan-3a-ol-20-one, also named tetrahydroprogesterone or allopregnanolone (ALLO) was one of the first most important steroid that was originally shown to act as neurosteroid. ALLO is synthesized through the action of the 5aR-3a-HSD, which converts P into DHP and subsequently, via a bidirectional reaction, into ALLO. NSs exert complex effects in the nervous system through 'classic', genomic, and 'non-classic', non-genomic actions. ALLO displays a rapid 'non-genomic' effect, which mainly involves the potent modulation of the GABA type A (GABA-A) receptor function. Recently a membrane receptor has been identified as target for ALLO effects, i.e. the membrane progesterone receptors (mPRs) that are able to activate a signalling cascade through G protein dependent mechanisms. By these ways, ALLO is able to modulate several cell functions, acting as neurogenic molecule on neural progenitor cells, as well as by activating proliferation and differentiation of glial cells in the central and peripheral nervous system. In this topic, we review the most recent acquisitions in the field of neurosteroids, focusing our attention on ALLO because its effects on the physiology of neurons and glial cells of the central and peripheral nervous system are intriguing and could potentially lead to the development of new strategies for neuroprotection and/or regeneration of injured nervous tissues and for the treatment of neuropsychiatric disorders.